Loneliness and orphanhood in contemporary families - Prokosz, Małgorzata (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
Orphanhood is a term that indicates the permanent or temporary separation of a child from the family of origin, i.e., biological, or social orphanhood. Contemporary analyses indicate, however, that orphanhood has become a multidimensional phenomenon and is also present in standard families. All orphanhood conditions are associated with loneliness, i.e., a child’s subjective feeling of lack of love, security, and support. Since orphanhood and loneliness of children can occur in every family, it is necessary to focus activities on support and help for those who need it most.
Keywords: family; orphanhood; solitude